AN ALYSIS OF MOBILE PHONE SERVICES QUALITY ELEMENTS IN THE REPUBLIC OF SERBIA - Tomašević, Dragana; Gašević, Dragana (International Journal of Economic Practice and Policy, 2019)
In modern business conditions, characterized by vast turbulences, uncertainty and dynamics and the survival, growth and development of companies is conditioned by focusing on ensuring a high level of service quality. It is considered that a company cannot achieve success in today’s business environment if it fails to provide services of superior quality. The ever-growing competition among mobile service operators imposes the need to identify key service quality elements. In order to remain competitive, communication service operators should provide services in accordance with the needs and stances of their users. The main objective of this research is to identify i.e. isolate the underlying factors that determine the quality of mobile phone services in the Rebublic of Serbia and determining their impact on customer satisfaction.